Emerging infections. - Scheld, W. Michael; Hooper, David C.; Hughes, James M., 1945- (Monograph, ASM Press., 2007)
This new volume is the seventh in a series of books based on ICAAC Symposia on Emerging Infections. It offers an updated review of new and emerging infectious diseases, including Avian Influenza (H5N1), Severe Acute Respiratory Syndrome (SARS), West Nile fever, and many others.